2018
DOI: 10.1007/s11046-018-0243-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Effects of Fluconazole and Voriconazole on Candida glabrata, Candida parapsilosis and Candida rugosa Biofilms

Abstract: Infections by non-albicans Candida species are a life-threatening condition, and formation of biofilms can lead to treatment failure in a clinical setting. This study was aimed to demonstrate the in vitro antibiofilm activity of fluconazole (FLU) and voriconazole (VOR) against C. glabrata, C. parapsilosis and C. rugosa with diverse antifungal susceptibilities to FLU and VOR. The antibiofilm activities of FLU and VOR in the form of suspension as well as pre-coatings were assessed by XTT [2,3-bis-(2-methoxy-4-ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
3
5
0
1
Order By: Relevance
“…Our results agree with a previous experimental murine infection by C. guilliermondii where voriconazole was reported to be experimentally effective (34). Previous studies also reported that C. parapsilosis exhibited good susceptibility to voriconazole in vitro (35,36). However, voriconazole failed to completely eradicate the infection in immunosuppressed mice in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Our results agree with a previous experimental murine infection by C. guilliermondii where voriconazole was reported to be experimentally effective (34). Previous studies also reported that C. parapsilosis exhibited good susceptibility to voriconazole in vitro (35,36). However, voriconazole failed to completely eradicate the infection in immunosuppressed mice in our study.…”
Section: Discussionsupporting
confidence: 92%
“…As far the antifungal susceptibility pro le of these yeasts the nding of high susceptibility for POS, VOR and ISA for all Candida spp. con rms the results of previous studies and suggests the usefulness of these drugs for treating tested these infections [44,45]. However, a low susceptibility for azoles and echinocandins were detected among non-albicans Candida spp.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, Madhavan et al [55] published results showing that fluconazole and voriconazole change the shape of Candida glabrata, Candida parapsilosis and Candida rugosa cells. Among other changes, these compounds cause dimples on the cell surface.…”
Section: Ergosterol Depletion and Surfactin Treatment Cause Changes Imentioning
confidence: 99%